Desenvolvimento de programa para dimensionamento estrutural de torres autoportantes para telecomunicação - Silverio, Acácio Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
The freestanding lattice towers are slender structures used to support the loads and raise the antennas of transmission of telecommunication, radio and television signals. These structures tolerate the loading applied efficiently, however, a malfunction in one of its parts can lead to the collapse of the structure, causing material losses, even of human lives. In the elaboration of the structural design of this type of tower, the sizing of the metallic profiles that make up the system takes in consideration the different actions that the structure can be submitted during its entire useful life. Therefore, this work has the objective of creating a program in computational language Python, which assists the professional responsible for the sizing, providing the force applied by the wind action, the force exerted by the proper weight of the structure, the tensions acting due to these forces and finally, the minimum steel area for the tubular section bars, according to the type of section of the tower (square or triangular equilateral). The program also provides the minimum areas being possible to compare with the pre-dimensioned ones. The results obtained in the practice with the elaboration of this program, is portrayed in the reduction of the design time and guarantee of effective sizing and coherent with the loads that the tower will support.
Monografia
Keywords: Estrutural de aço; Ação do vento; Dimensionamento; Programação em Python; ENGENHARIAS::ENGENHARIA CIVIL